Pengaruh Game Baamboozle Terhadap Minat Belajar Siswa pada Mata Pelajaran Geografi di SMA Negeri 8 Bengkulu Utara - Triwulandari, Septi; Rahmi, Lailatur (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the influence of the baamboozle game on geography subjects on students' learning interest at SMA Negeri 8 North Bengkulu. This research method uses quantitative research with an experimental type. The sample determination technique uses purposive sampling. The sample size was 68 respondents. Divided into experimental and control groups. Some of the data collection techniques used in this study are questionnaires, observations, and documentation. Data analysis techniques include normality tests, homogeneity, n-Gain, and hypothesis tests. The results of the analysis showed that there was an effect of the baambozle game on the learning interest of geography students of SMA Negeri 8 North Bengkulu in studying the subject. The learning interest of students in experimental classes that use baamboole games as a medium is more effective compared to the traditional classroom method (lecture). It shows the influence of the baamboozle game on students' learning interest in the experimental class. The independent sample t-test hypothesis test showed significant values of 0.004 < 0.050. It can be concluded that there is an influence of the baamboozle game on students' interest in learning geography subjects at SMA Negeri 8 North Bengkulu